Students' Difficulties in Writing Literature Review Section of Postgraduate Students of Two State Universities in West Java - Satriani, Intan; Sakhiyya, Zulfa; Widhiyanto, Widhiyanto; Bahri, Seful (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2024)
It takes a lot of work to write an effective thesis in an academic context in order to graduate. Writing a thesis is a unique genre with its own rules, guidelines, and conventions. In the case of graduate and master degree students, they are not only have to meet the requirements of this genre, but also the language used which different with their first language, in this case is English. Therefore, this study aimed at analyzing difficulties in writing literature review sections of English major master’s thesis written by Indonesian EFL learners. This study applied qualitative descriptive as research method with six interviewees. The results of this study found that there were five difficulties. The difficulties were deciding subtopic of literature review section, finding relevant and reputable journal that support the research, synthesizing skill in completing literature review, formulating pattern or move in writing literature review section, and constructing argument and knowing the function of literature review. Addressing these difficulties requires following actions. They are enhancing training in research methods, better access to academic resources, and providing a guidance book especially in writing literature review.